Antibacterial Activity of Centella asiatica N-Hexane Fraction against Pseudomonas aeruginosa Clinical Isolates - Larasati, Alifia Amanda; Rosyunita; Fathul Djannah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Pseudomonas aeruginosa is a gram-negative bacterium that causes infections with high morbidity and mortality rates. Currently, treatment of P. aeruginosa infections is a major challenge due to its ability to resist various available antibiotics. Among the herbal plants with potential as a novel antibacterial agent is Centella asiatica. Nevertheless, the n-hexane fraction has never been used to investigate the antibacterial activity of C. asiatica as a herbal plant. This study aims to determine the antibacterial activity of the n-hexane fraction of C. asiatica by sokhletation extraction method against clinical isolates of P. aeruginosa and determine the bioactive compounds contained. The method used was disc diffusion (Kirby-Bauer test) with concentrations of 5,000 ppm, 7,500 ppm, and 10,000 ppm, positive control using 10 μg colistin and negative control using 10% DMSO. The results showed that the three test concentrations of C. asiatica n-hexane fraction formed a clear zone of 2.50 mm; 4.77 mm, and 2.43 mm respectively and contained flavonoid and steroid compounds. Statistically, Kruskal-Wallis test showed that there was a significant effect of changing the concentration of n-hexane fraction on the diameter of the inhibition zone. However, Post hoc test using Mann-Whitney showed that the three concentration series had significant differences in inhibition against the positive control. Overall, the n-hexane fraction of C. asiatica had lower antibacterial activity compared to the positive control of colistin. In future studies, it is necessary to test antibacterial activity using a more varied concentration series and other antibacterial activity test methods.